Pelaksanaan KRPL dalam Meningkatkan Ketahanan Pangan di Kelurahan Cipari Kecamatan Cigugur Kabupaten Kuningan - Aldiansyah, Rizky; Ayuda, Wahyu; Wijaya, Nanda Sukma; Salta, Salta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Sustainable Food Home Area (KRPL) is a concept that utilizes the yard around the house with varios types of plants. So that people get the benefits of getting food independently, can fulfill nutrition, and provide additional income independently. The purpose of this research is to find out how food availability and find out how to improve household food security in Cipari Village, Cigugur District, Kuningan Regency. The implementation of the Sustainable Food Home Area program begins with the search for raw materials to make a plant such as polybags, soil, rice husks, cow dung, and chili seeds, then proceed with the process of mixing planting media, namely soil, dried cow dung, and rice husks after mixing the plant media, then inserting the planting media into the polybag and inserting chili seeds into the polybag that has been filled by the planting media. The result of this program is that there are 200 plant seeds that were successfully made and successfully distributed to Cipari Village residents, especially in the Sukasari Rw 01, Rt 04 environment. The Sustainable Food Home Area Program is a program that can increase food security in every home in the Sukasari environment, especially Rt 04 and in this work program we can produce a product in the form of chili plant seeds.